DNA cleavage by Type ISP Restriction–Modification enzymes is initially targeted to the 3′-5′ strand - van Aelst, Kara (Oxford University Press, 2013)
The mechanism by which a double-stranded DNA break is produced following collision of two translocating Type I Restriction–Modification enzymes is not fully understood. Here, we demonstrate that the related Type ISP Restriction–Modification enzymes LlaGI and LlaBIII can cooperate to cleave DNA following convergent translocation and collision. When one of these enzymes is a mutant protein that lacks endonuclease activity, DNA cleavage of the 3′-5′ strand relative to the wild-type enzyme still occurs, with the same kinetics and at the same collision loci as for a reaction between two wild-type enzymes. The DNA nicking activity of the wild-type enzyme is still activated by a protein variant entirely lacking the Mrr nuclease domain and by a helicase mutant that cannot translocate. However, the helicase mutant cannot cleave the DNA despite the presence of an intact nuclease domain. Cleavage by the wild-type enzyme is not activated by unrelated protein roadblocks. We suggest that the nuclease activity of the Type ISP enzymes is activated following collision with another Type ISP enzyme and requires adenosine triphosphate binding/hydrolysis but, surprisingly, does not require interaction between the nuclease domains. Following the initial rapid endonuclease activity, additional DNA cleavage events then occur more slowly, leading to further processing of the initial double-stranded DNA break.